Nine-year follow-up of a case of Grzybowski type multiple keratoacanthomas and failure to demonstrate human papillomavirus - Haas, Norbert P.; Schadendorf, Dirk (British journal of dermatology, 2002)
We describe a patient with a 9-year history of generalized eruptive keratoacanthoma (KA) of the Grzybowski type whose multiple skin lesions showed steady progression, resulting in a sclerotic, mask-like facial expression and ectropion. Eleven tumour biopsies representing lesions of different stages and localizations (erupting and regressing KAs, biopsies from non-involved light-protected and light-exposed skin, dermatosclerosis and squamous cell carcinomas) were analysed for human papillomavirus (HPV) sequences using a polymerase chain reaction approach capable of detecting the majority of all presently known HPV genotypes. None of the biopsy specimens proved to be HPV-positive, although HPV was detected in weakly and heavily affected control specimens by the method applied. These findings suggest an HPV-independent aetiology of this rare type of multiple KA.
Gesehen am 17.11.2020